MspI polymorphism of bovine growth hormone gene on locus-2 and its effect on daily gain of body weight - SUTARNO SUTARNO; ARIS JUNAIDI; BAHARUDIN TAPPA (Society for Indonesian Biodiversity, 2005)
The objectives of the research were to identify growth hormone gene variation of Indonesian native cattle, PO cattle, and to know the effect of the variation on growth rate (daily gain) of the cattle. White blood cells were extracted from the samples of total blood by buffy coat method. DNA was then extracted from white blood cells using Wizard Genomic Purification kit. PCR-RFLP using MspI restriction enzyme was employed to detect polymorphic site on locus 2 of GH gen continued with sequencing for some representative genotypes. Phenotypicdata of growth rate (daily gain) measured for 90 days, while sex and age were used as supporting phenotypic data. All data were then analysed statistically using Anova model implemented in JMP program from SAS. The result of the analysis indicated that MspI polymorphism affect growth rate significantly (P=0.01), in which MspI (+-) genotype resulted in best growth of PO cattle. Age and sex were also affect growth of the cattle.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: PO cattle, PCR-RFLP, GH gene, growth